Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Smartphone Iphone 12 Di Kota Bandung - Yolanda Firdayanti; Farah Oktafani (RELASI : JURNAL EKONOMI, 2023)
The purpose of this study is to analyze the customer perception of smartphone iPhone 12 in Bandung City on Product Quality and Product Price on Purchase Decisions partially and simultaneously. The method that is used in this study is descriptive quantitative method. Sampling was carried out using a non-probability sampling method with a purposive sampling sample. The sample of this research was iPhone 12 users who live in Bandung City, with a total of 100 respondents. The analysis data technique that was used in this research was multiple linear regression. Based on the results of the T-test in this research, product quality and price variable have a significant influence on purchasing decisions partially on iPhone 12 smartphone users in Bandung City. Furthermore, based on the results of the F-test in this study, product quality and product price variables have a significant influence on purchasing decisions simultaneously on iPhone 12 smartphone users in Bandung City. Therefore, based on the result of the coefficient determination, the R Square has a score of 0.696, which means that the independent variables, product quality and product price affect the purchasing decisions by 69.6% while the remaining 30.4% is the contribution of the influence of other variables outside this study.